2018
DOI: 10.1021/acs.jpclett.8b03534
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transitions Responsible for C60+ Diffuse Interstellar Bands

Abstract: Diffuse interstellar bands (DIBs) are puzzling absorption features believed to contain critical information about molecular evolution in space. Despite the fact that C 60 + recently became the first confirmed carrier of several DIBs, the nature of the corresponding transitions is not understood. Using electronic structure methods, we show that the two strong C 60 + DIBs cannot be explained by electronic transitions to the two different excited 2 E 1g states or the two spin−orbit components of the lowest 2 E 1g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…The results of our TPES of C 60 imply a different symmetry of the ground state ion than calculations seem to favor, which is in line with some other previous experimental findings. 39,74 Although this work implies that the ground state of the C 60 + ion belongs to the D 3d symmetry group rather than the D 5d symmetry group, the recent theoretical progress 43 in assigning the transitions at the heart of the DIBs that have been assigned to C 60 + , are not diminished -on the contrary -as both D 5d and D 3d symmetry groups undergo the same pseudo-JT distortion to give rise to C 2h symmetry and, moreover, there does seem to be a connection between the DIBs assigned to C 60 + and the most intense structure we observe in the second photoelectron band in our recorded TPES. This does not tell the whole story, however, as the energetics of the 6g g and 10h g excited states have not been definitively accounted for and it is likely that their structure in the second photoelectron band is due to photoionization converging to unresolvable vibrational modes of these states.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results of our TPES of C 60 imply a different symmetry of the ground state ion than calculations seem to favor, which is in line with some other previous experimental findings. 39,74 Although this work implies that the ground state of the C 60 + ion belongs to the D 3d symmetry group rather than the D 5d symmetry group, the recent theoretical progress 43 in assigning the transitions at the heart of the DIBs that have been assigned to C 60 + , are not diminished -on the contrary -as both D 5d and D 3d symmetry groups undergo the same pseudo-JT distortion to give rise to C 2h symmetry and, moreover, there does seem to be a connection between the DIBs assigned to C 60 + and the most intense structure we observe in the second photoelectron band in our recorded TPES. This does not tell the whole story, however, as the energetics of the 6g g and 10h g excited states have not been definitively accounted for and it is likely that their structure in the second photoelectron band is due to photoionization converging to unresolvable vibrational modes of these states.…”
Section: Discussionmentioning
confidence: 91%
“…81 In terms of an exact assignment of the features of the second photoelectron band, however, the more relaxed rules of direct ionization add a level of complication since more transitions from the ground neutral state to both JT split electronic states are possible, as compared to the limited number of two bright states. 43 With the added congestion from possible vibrational progressions and our current energy resolution, we can only note that the predicted JT splitting is too small to account for the peak separation in Table 3, so that most likely, and based on the calculated ionization energies, the first two bands can be attributed to direct ionization to the 6g g and 10h g states. Thus, the third band might represent vibrational progression on the cation, as already postulated.…”
Section: Threshold Photoelectron Spectrum (Tpes)mentioning
confidence: 92%
See 1 more Smart Citation
“…The near-infrared absorptions of C + 60 have been assigned to the lowest energy 2 E 1g ← X 2 A 1u electronic transition (in D 5d ). Recent theoretical work indicates that C + 60 undergoes a Jahn-Teller distortion from the D 5d minimum such that the upper 2 E 1g state is split into two components with A g and B g symmetry (in C 2h ), leading to two transitions separated by 41 cm −1 (see Figure 3 in [34]). Transitions from the A u ground electronic state to these components are believed to be responsible for the absorption bands of C + 60 at 10,378 and 10,438 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, they showed that both the 9577Å and 9632Å absorptions are caused by one C + 60 structural isomer, and arise from the lowest vibrational level of the same ground electronic state ( 2 A 1u in D 5d ). Recent theoretical work assigned these as transitions to two components ( 2 A g and 2 B g in C 2h ) of the Jahn-Teller split excited 2 E 1g state, with the next two absorption bands to higher energy involving excitation of the lowest frequency cage vibration (∼ 230 cm −1 ) [76]. The widths of the laboratory bands were found to be similar, but slightly narrower, than the interstellar ones, with the appearance of the profile below 10 K caused by internal conversion.…”
Section: Gas-phase Spectroscopymentioning
confidence: 99%